Hydraulic Analysis of Fallujah Water Network By Using a Program EPANET - A. MOULOOD, IBTIHAL (Anbar Journal of Engineering Sciences, 2010)
This search includes analysis of Fallujah water network that are fed from the old drinking water treatment station in Fallujah , which provides citizens in residential areas (AL-Jolan District, AL- Mu’tasim district, AL-Andalus district) by drinking water by using a program (EPANET) in the hydraulic network analysis .It was found their are lack in the required amount of water which estimated by about 20% due to oldness of the station and the lack of expansion by estimation the population growth the city. After input required the data in the analysis in got the results, it was noted that the three areas were getting the amount of required water, but the speed of water in the pipe network was very low and below the allowable limits (less than 1 m / s), this means that the design of the network has not takes into account the economic side and health status. The results were compared with the situated case and found a lack of water amount reaching the people as a result of trespasses and interruptions which occurring in the network, as well as the head pressure which reach the supply points fall within the permissible limits where ranging between (38-48 m) but the use of water pumps in homes lead to decrease the head pressure whenever the node far away from the drinking water station.